Pectoralis Major Flap for Chest Wall Reconstruction: Anatomical Reliability, Technical Variants, And Contemporary Indications - Brian Eduardo Apodaca Escalante; Alberto Sanchez Navarro Bermejo (International Journal of Medical Science and Clinical Research Studies, 2026)
Chest wall reconstruction requires restoration of stable coverage, protection of intrathoracic structures, control of infection or dead space, and preservation of respiratory mechanics. The pectoralis major flap remains one of the principal regional options for anterior and upper chest wall reconstruction because of its proximity, reliable vascular anatomy, broad arc of rotation, and ability to provide well-vascularized tissue in contaminated, irradiated, or oncologic wounds. Classically based on the thoracoacromial pedicle, the flap can be advanced, rotated, split, islanded, transposed bilaterally, or designed as a musculocutaneous flap depending on the defect. Internal mammary perforator–based designs further expand its versatility. The pectoralis major is particularly useful for sternal wound infection, anterior chest wall defects, sternoclavicular defects, manubrial reconstruction, supraclavicular coverage, and selected oncologic or radiation-related defects. Although free tissue transfer is increasingly used for large or complex defects, pedicled pectoralis major flaps remain highly relevant because they provide rapid, dependable reconstruction without microvascular anastomosis. Current evidence supports their reliability, but comparative data remain limited, and long-term functional outcomes, donor-site morbidity, shoulder function, quality of life, and cost-effectiveness require further study.